Micro finance to the poor: a tool for poverty alleviation and women empowerment - Rao, K. Srinivasa (2008)
Macro-finance is a financial service of small quantity provided by financial institutions to the poor. Globally, over a billion poor people are still without access to formal financial services and 200 million of them live in India. In recognition of the potential of micro-finance to address diverse aspects of poverty the United Nations launched the International year of Micro credit 2005. The United Nations Millennium Summit courageously adopted the Millennium Development Goals. the most bold and important of these goals is halving world poverty by 2015. This paper traces the evolution and history of micro-finance in India. Over the years, micro-finance programmes in India have grown, providing a wide range of services to meet the economic and social needs of its citizens, mostly to the poor women and weaker sections. - Reproduced.
Keywords: Nongovernmental organizations; Finance; Women; Poverty